Quantification of Sequential Chlorinated Ethene Degradation by Use of a Reactive Transport Model Incorporating Isotope Fractionation - Van Breukelen, Boris M.; Hunkeler, Daniel; Volkering, Frank (My University, 2005)
Compound-specific isotope analysis (CSIA) enables quantification of biodegradation by use of the Rayleigh equation. The Rayleigh equation fails, however, to describe the sequential degradation of chlorinated aliphatic hydrocarbons (CAHs) involving various intermediates that are controlled by simultaneous degradation and production. This paper shows how isotope fractionation during sequential degradation can be simulated in a 1D reactive transport code (PHREEQC-2). 12C and 13C isotopes of each CAH were simulated as separate species, and the ratio of the rate constants of the heavy to light isotope equaled the kinetic isotope fractionation factor for each degradation step. The developed multistep isotope fractionation reactive transport model (IF-RTM) adequately simulated reductive dechlorination of tetrachloroethene (PCE) to ethene in a microcosm experiment. Transport scenarios were performed to evaluate the effect of sorption and of different degradation rate constant ratios among CAH species on the downgradient isotope evolution. The power of the model to quantify degradation is illustrated for situations where mixed sources degrade and for situations where daughter products are removed by oxidative processes. Finally, the model was used to interpret the occurrence of reductive dechlorination at a field site. The developed methodology can easily be incorporated in 3D solute transport models to enable quantification of sequential CAH degradation in the field by CSIA.